1988
DOI: 10.1002/bbpc.198800327
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Analysis of Quartz Oscillators, Contacted on One Side with a Liquid

Abstract: We use a vector analyzer to investigate the impedance of a quartz oscillator, one face of which is exposed to a liquid. An aqueous LiCl – solution can be used to vary density and viscosity of the liquid over a wide range. The solution acts as an additional impedance with as well a real as an imaginary part. Furthermore, different electrical driver circuits have been used to excite the crystal vibrations. In most cases, our experimental results deviate from the predicted dependence of the crystal frequency from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…Here, we present and validate a new method for measuring the deformation of nm-sized liposomes adsorbing on surfaces. Although it is based on deducing the height of surface-adsorbed liposomes (labeled as h in Figure 1) from QCM [17][18][19][20][21] measurements, it does not rely on a model. Previously, we showed that this method reliably and quantitatively yields the size of the adsorbed particles for stiff particles that do not deform upon adsorption; in that case, h ∼ 2R (Figure 1(a)), where R is the radius of particles in solution (e.g., measured with dynamic light scattering).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present and validate a new method for measuring the deformation of nm-sized liposomes adsorbing on surfaces. Although it is based on deducing the height of surface-adsorbed liposomes (labeled as h in Figure 1) from QCM [17][18][19][20][21] measurements, it does not rely on a model. Previously, we showed that this method reliably and quantitatively yields the size of the adsorbed particles for stiff particles that do not deform upon adsorption; in that case, h ∼ 2R (Figure 1(a)), where R is the radius of particles in solution (e.g., measured with dynamic light scattering).…”
Section: Introductionmentioning
confidence: 99%
“…A parallel capacitance C p , caused by the electrodes on the quartz and any stray capacitance 3. A resistive component R 0 The resistance R 0 is a measure of mechanical losses from the vibrating quartz, and it therefore reflects the viscoelastic properties of the contact- ing liquid [240], [241] or a deposited film [242]. Surface roughness also influences the value of R 0 [243].…”
Section: Fundamental Principles and Basic Types Of Transducersmentioning
confidence: 99%
“…Likewise, immobilized peptide molecules may alter the tertiary shape by changing the ionic strength, resulting in a different surface roughness. Changes in the vibrating mass correspond to changes in the self-inductance L 0 [244], [245]. Thus, the resonance frequency of the motional arm ( f m ; see Fig.…”
Section: Fundamental Principles and Basic Types Of Transducersmentioning
confidence: 99%
“…Among the many piezoelectric materials, α-quartz is most commonly studied and used as piezoelectric oscillator, because desired features can be achieved through various cuts of its native crystals [2,3,[27][28][29]:…”
Section: Transducer-oscillator Materials Configurationsmentioning
confidence: 99%
“…In such a case, the apparent mass changes calculated from the Sauerbrey equation may be erroneous. However, impedance measurements and QCM studies of systematic thickness variations can help to interpret the observed frequency shifts [7,15,[29][30][31][32][34][35][36][37][38][39][40][42][43][44].…”
Section: Quartz Oscillator Coated With a Viscous Surfacementioning
confidence: 99%